An effective way to reduce energy loss and enhance open-circuit voltage in polymer solar cells based on a diketopyrrolopyrrole polymer containing three regular alternating units. Issue 34 (10th August 2016) - Liu, Yahui; Li, Guangwu; Zhang, Zhe; Wu, Liangliang; Chen, Jianya; Xu, Xinjun; Chen, Xuebo; Ma, Wei; Bo, Zhishan
Abstract : A planar DPP-based polymer containing three regular alternating units exhibits a good photovoltaic performance with a high PCE of 9.02% and a large V oc of 0.86 V. Abstract : A novel diketopyrrolopyrrole (DPP)-based conjugated polymer (PCDPP ) was designed, synthesized and used as a donor material for polymer solar cells (PSCs). By increasing the planarity of polymer chains and reducing the energy loss in devices, we have simultaneously acquired a high short-circuit current ( J sc ) and a large open-circuit voltage ( V oc ) in PSCs based onPCDPP, which is a regular alternating ternary conjugated polymer. This polymer has a medium optical band gap (1.55 eV) with low-lying HOMO and LUMO energy levels. In addition, PCDPP exhibits a very good planarity from density functional theory (DFT) calculations and forms a fibrillar network in the active layer of solar cells. Because of these integrated favourable effects, PCDPP -based photovoltaic devices exhibit a high power conversion efficiency (PCE) of 9.02% which is among the highest values reported so far for devices based on DPP-containing polymers. More importantly, the V oc of ourPCDPP -based devices can reach as high as 0.86 V, which is much higher than that (<0.7 V) of high-efficiency solar cells based on other DPP polymers. These results provide a promising way to minimize the energy loss and to realize high V oc and J sc values at the same time in devices to obtain high power conversion efficiencies.